Eyespots in a Reversible Setting. (February 2013) - Deręgowski, Jan B; Gray, Colin D
When eyespots were presented on a reversible figure, the total duration for which elements bearing the eyespots were seen as closer to the observer was found to be greater than the total for counterpart elements. It is speculated that the tendency to see eyespots as nearer than they really are is related to the manner in which they are responded to in nature.